Estimation of vitamin D receptor gene polymorphism in Type 2 Diabetes Mellitus patients in Erbil city - Maulood, Kalthum Asaaf (Cellular and Molecular Biology, 2021)
Type 2 diabetes mellitus (T2DM) is a global problem. Recent studies confirmed the association of genes and different single nucleotide polymorphisms with T2DM occurrence and progress. This study was aimed to estimate the vitamin D receptor (VDR) gene polymorphism in Type 2 Diabetes Mellitus patients in Erbil city. The results showed that the Body mass index (BMI), Systolic blood pressure and Diastolic blood pressure were significantly higher in the diabetic group compared to the control group (P<0.05). In addition, the percent of Glycated hemoglobin (HbA1c), Fasting blood glucose (FBG), and Homeostatic model assessment for insulin resistance (HOMA-IR) were significantly higher in the diabetic group compared to the control group (P<0.05). Among different parameters of lipid profile, only Low-density lipoprotein (LDL) was significantly higher in the diabetic group compared to the control group. It was found that FBG value was significantly higher in patients with GA and AA genotypes of BsmI compared with healthy controls. Patients with the GA genotype of BsmI had a higher value of triglyceride compared to healthy individuals. Patients with all ApaI genotypes had higher FBS values than controls. There were not observed any signi?cant associations among the BsmI and ApaI polymorphisms and the risk of T2DM. In conclusion, no evidence was found for the association between two VDR polymorphisms and T2DM patients in Erbil city.